Anthropometric Study of Nasal Parameters in Iranian University Students - Fatemeh Tahmasebi; Maryam Khanehzad; Soheila Madadi; Gholamreza Hassanzadeh (Negah Institute for Scientific Communication, 2015)
Introduction: Nose morphology depends on gender, ethnicity, and environmental conditions. It can be used in identification of the race and sex of persons whose identity is unknown. Nasal index is a useful tool in anthropometry. Methods: In this study, nasal parameters of Iranian males and females students were measured (nasal height, nasal width, and nasal index). This study was conducted on 200 medical students of Tehran University, Tehran, Iran. Subjects were 100 males and 100 females, aged 18-30 years. The nasal height and width were measured by a sliding vernier calliper and the nasal index was accordingly calculated. Results: Our data showed that the mean nasal index for males and females were 68.91±8.11 and 66.05±7.53, respectively. So, nose of Iranian people is leptorrhine type. The mean nasal index in males was significantly (P≤0.05) higher than that in females. Conclusion: The result of this study could be employed in the detection of gender in forensic medicine and rhinoplasty surgery.